Chandra’s Insights into SN 2023ixf - Poonam Chandra; Roger A. Chevalier; Keiichi Maeda; Alak K. Ray; Nayana A. J. (The Astrophysical Journal Letters)
We report Chandra-ACIS observations of supernova (SN) 2023ixf in M101 on day 13 and 86 since the explosion. The X-rays in both epochs are characterized by high-temperature plasma from the forward shocked region as a result of circumstellar interaction. We are able to constrain the absorption column density at both Chandra epochs, which is much larger than that due to the Galactic and host absorption column, and we attribute it to absorption by the circumstellar matter in the immediate vicinity of SN 2023ixf. Combining our column density measurements with the published measurement on day 4, we show that the column density declines as t ^−2 between day 4 to day 13 and then evolves as t ^−1 . The unabsorbed 0.3–10 keV luminosity evolves as t ^−1 during the Chandra epochs. On the Chandra first epoch observation, when the SN was 13 days old, we detect the Fe K α fluorescent line at 6.4 keV indicating presence of cold material in the vicinity of the supernova. The line is absent on day 86, consistent with the decreased column density by a factor of 7 between the two epochs. Our analysis indicates that during 10–1.5 yr before explosion, the progenitor was evolving with a constant mass-loss rate of 5.6 × 10 ^−4 M _⊙ yr ^−1 .